How can data quality and other relevant system migration parameters & processes enhance the success rate of IT projects in software migrations? A case study at UBS A.G. - Bertaud, Anna (My University, 2022)
Keeping competitive advantage is a continuous and ubiquitous process: not only does an organization require great architecture to support daily activities, but the business processes must be defined to optimize the costs, the time and the satisfaction of the end user. As most of the daily activities are now digital or being supported by digital solutions, IT project management is a key process for a company: unique in nature and often intangible, it requires a clear comprehension of the business processes, a perfect organization and tools to maximize the outcomes. Unfortunately, IT projects are prone to failure due to high uncertainty and the diversity of skills required (PM, technical, financing…), and even if some signs might highlight, from the start, that the project is not on the right path, no general tool exists to measure the potential outcomes. In this paper, the author has developed a predictive tool as a case study in her internship’s company UBS A.G.: by selecting key factors through extensive literature review and data analysis, the algorithm outputs a decision tree to underline not only the prediction of the project but understand which factors weights in more than other. High accuracy and precision on successful outcomes confirmed that complexity influences the outcomes the heaviest. Validating these findings through interviews of highly-skilled employees, the discussion determined the steps in IT projects where risks can appear and suggests possible future intiatives to improve the processes and satisfaction. The case study offers a complete research on the process and outcomes of IT projects which can be applied on a broader horizon at UBS A.G. and possibly other companies.
Keywords: Data quality, enhancement, IT projects, predictive tool, system parameters